Thirty-five–year Trends in First-time Hospitalization for Hip Fracture, 1-year Mortality, and the Prognostic Impact of Comorbidity: A Danish Nationwide Cohort Study, 1980–2014. Issue 6 (November 2017) - Pedersen, Alma B.; Ehrenstein, Vera; Szépligeti, Szimonetta K.; Lunde, Astrid; Lagerros, Ylva Trolle; Westerlund, Anna; Tell, Grethe S.; Sørensen, Henrik T.
Abstract : Background: We examined trends in hip fracture incidence in Denmark from 1980 to 2014, trends in subsequent 1-year mortality, and the prognostic impact of sex, age, and comorbidity. Methods: This nationwide cohort study prospectively collected data from population-based Danish registries. We included 262, 437 patients with incident hip fracture and assessed comorbidity using the Charlson Comorbidity Index (CCI). Results: Despite slight increases in incidence rates (IRs) of hip fracture up to the mid-1990s, the annual IR decreased by 29% from 1980 to 2014 in women but remained stable in men. Decrease affected all age groups. IR decreased in patients without comorbidity but increased with increasing comorbidity (13% in patients with moderate and 510% in patients with very severe comorbidity). Adjusted mortality rate ratios (MRRs) following hip fracture in 2010–2014 compared with 1980–1984 were 0.68 (95% confidence interval [CI] = 0.65, 0.71) within 30 days and 0.63 (95% CI = 0.61, 0.66) within 31–365 days. The mortality decreased up to 40% irrespective of comorbidity. Compared with patients with no comorbidity, those with very severe comorbidity had adjusted MRRs of 2.48 (95% CI = 2.39, 2.56) and 2.81 (95% CI = 2.74, 2.88) within 30 days and 31–365 days post-hip fracture, respectively. Conclusions: Although the incidence rate of hip fracture increased substantially with increasing comorbidity, the following 1-year mortality decreased by 40% from 1980 through 2014 irrespective of sex, age, and comorbidity level, suggesting improvement in both treatment and rehabilitation of patients with hip fracture. Comorbidity burden was, however, a strong prognostic factor for 1-year mortality after hip fracture. Abstract : Supplemental Digital Content is available in the text.